Sustainable process engineering: concepts, strategies, evaluation and implementation - Brennan, David (David J.) (Singapore : Pan Stanford Publishing Pte. Ltd., 2013)
'This book introduces chemical engineering students to key concepts, strategies, and evaluation methods in sustainable process engineering. It is intended to supplement chemical engineering texts in fundamentals and design, rather than replace them. Competence in fundamental science and engineering, including mass and energy balances, is assumed. The key objectives are to (i) widen system boundaries beyond a process plant to include utility supplies, interconnected plants, wider industry sectors, and entire product life cycles; (ii) identify waste and its sources in process and utility systems and adopt waste minimisation strategies; (iii) broaden evaluation to include technical, economic, safety, environmental, social, and sustainability criteria and to integrate the assessments; and (iv) broaden the engineering horizon to incorporate planning, development, design, and operations.'--Back cover.
Includes bibliographical references and indexes.
Keywords: Green manufacturing & systems engineering; Sustainable engineering; Renewable energy sources; Refuse and refuse disposal; Chemical processes; Chemical engineering; Chemical engineering -- Economic aspects; Production planning; Manufacturing processes; Chemical industry